Mechanical and electrical performance characterization of partial mock-up of the ITER PF6 coil tail. (December 2017) - Zhang, Z.; Song, Y.; Wu, H.; Zhang, M.; Xie, Y.; Hu, B.; Liu, F.; Shen, G.; Wu, W.; Lu, K.; Wei, J.; Bilbao, M.; et al.
Highlights: Fatigue property of ITER PF6 coil tail partial mock-up at 77 K was characterized. HV performance of the mock-up was assessed before and after the fatigue test. Design of PF6 coil tail was confirmed with the mechanical and electrical results. Abstract: International Thermonuclear Experimental Reactor (ITER) is a full superconducting coil tokamak. The tail is an important component of Poloidal Field (PF) coil, of which the main functions are to provide the electrical isolation and transfer the longitudinal load from the last turn to the last-but-one turn. The paper focuses on an optimized mechanical structure of PF6 coil tail, which is made up of two main parts. One was welded to the last turn and the other was welded to the last-but-one turn. Both of them were connected by the mechanical coupling. The electrical isolation between the two parts was maintained by a strap made of insulating composite. In addition, as the PF6 coil is operated under the cyclic electromagnetic load during the tokamak operation, the fatigue property of the tail should be assessed and qualified at low temperature. Moreover, taking into consideration the complexity of the insulation winding process which is performed in a confined space, the wrapping process of the insulation needs to be established. Meanwhile, the high voltage (HV) tests of the tail insulation, including the direct current (DC) and alternating current (AC) tests, need to be assessed before and after the fatigue test. In this paper, a fully bonded PF6 coil tail partial mock-up (not including the weld of the tail to the last conductor turn) was designed and manufactured by simulating the actual manufacturing processes. In addition, the fatigue tests on the sample were carried out at 77 K, and the results showed the sample had good and stable fatigue properties at cryogenic temperature. The HV tests before and after the fatigue test, also including the final 30 kV breakdown DC test after the fatigue test, were carried out. The test results satisfied the requirements of ITER and were discussed in depth. Finally, the sample was destructively inspected to validate the integrity of the insulation by mechanical cross sectioning, and no voids and cracks were observed. Therefore it can be verified from the test results that the designed PF6 coil tail has good comprehensive properties, which can be applied to the formal production of the PF6 coil.